Diversity of germination strategies and seed dormancy in herbaceous species of campo rupestre grasslands - Le Stradic, Soizig; Silveira, Fernando A. O; Buisson, Elise; Cazelles, Kévin; Carvalho, Vanessa; Fernandes, G. Wilson (Austral ecology, 2015)
The effects of fire on the vegetation vary across continents. However, in Neotropical fire‐prone grasslands, the relationship between fire and seed germination is still poorly understood, while their regeneration, especially after strong anthropogenic disturbance, is challenging for their conservation. In the present study, we assessed diversity of germination strategies in 15 dominant herbaceous species from Neotropical altitudinal grasslands (locally known as campos rupestres). We exposed seeds to several fire‐related treatments. We also compared germination between regularly and post‐fire fruiting species. Finally, we investigated the diversity of dormancy classes aiming at better understanding the biogeography and phylogeny of seed dormancy. Germination strategies varied among families. Velloziaceae and Xyridaceae produced non‐dormant, fast‐germinating seeds. Cyperaceae and Poaceae showed an extremely low or null germination due to a high proportion of unviable or embryo‐less seeds. The seeds of campo rupestre grasslands are fire resistant, but there is no evidence that fire triggers germination in this fire‐prone ecosystem. Although heat and charred wood did not promote germination, smoke enhanced germination in one grass species and decreased the mean germination time and improved synchrony in Xyridaceae and Velloziaceae. Fire had a positive effect on post‐fire regeneration by stimulating fruit set in some Cyperaceae and Poaceae species. These species produced faster germinating seeds with higher germination percentage and synchrony compared to regularly fruiting Cyperaceae and Poaceae species. This strategy of dispersion and regeneration seems to be an alternative to the production of seeds with germination triggered by fire. Physiological dormancy is reported for the first time in several clades of Neotropical plants. Our data help advance the knowledge on the role of fire in the regeneration of Neotropical grasslands.